Pengembangan Modul Analisis Vektor Terintegrasi Media Pembelajaran Prezi - Yunis Sulistyorini; Dian Fitri Argarini (Program Studi Pendidikan Matematika IKIP PGRI Jember, 2019)
The study aims to describe the development and produce an integrated vector analysis module with Prezi that is valid, practical and effective. Development refers to the 4D development model, that is define, design, develop, and disseminate. Disseminate stage is not done in this research because the use of module is only limited to undergraduate students of Mathematics Education IKIP Budi Utomo Malang. The developed Vector Analysis module is feasible of use that satisfy all three aspects, namely validity, practicality and effectiveness. The developed vector analysis module has several advantages. First, connect the concept of vector analysis with real life. Second, integrated with prezi-based learning media that support deeper understanding of the concept of vector analysis.